A Synthetic, Transiently Thermoresponsive Homopolymer with UCST Behaviour within a Physiologically Relevant Window. Issue 23 (30th April 2019) - Zhang, Zhiyue; Li, Hui; Kasmi, Sabah; Van Herck, Simon; Deswarte, Kim; Lambrecht, Bart N.; Hoogenboom, Richard; Nuhn, Lutz; De Geest, Bruno G.
Abstract: Interactive materials that can respond to a trigger by changing their morphology, but that can also gradually degrade into a fully soluble state, are attractive building blocks for the next generation of biomaterials. Herein, we design such transiently responsive polymers that exhibit UCST behaviour while gradually losing this property in response to a hydrolysis reaction in the polymer side chains. The polymers operate within a physiologically relevant window in terms of temperature, pH, and ionic strength. Whereas such behaviour has been reported earlier for LCST systems, it is at present unexplored for UCST polymers. Furthermore, we demonstrate that, in contrast to LCST polymers, in aqueous medium the UCST polymer forms a coacervate phase below the UCST, which can entrap a hydrophilic model protein, as well as a hydrophobic dye. Because of their non‐toxicity, we also provide in vivo proof of concept of the use of this coacervate as a protein depot, in view of sustained‐release applications. Abstract : Homopolymers were designed that exhibit upper critical solution temperature (UCST) behaviour under physiologically relevant conditions. In response to a hydrolysis reaction in the side chain, the polymers gradually lose their UCST properties. Below the UCST, the polymers form coacervate droplets, which can be used for biomedical purposes.